FEMORAL NECK FRACTURES: THE BALANCING ACT BETWEEN FIXING OR REPLACING - T, Shival; Ahmed, MohammedHarris; Kunalan, Sasidaran; Mohamad, Fazir (International Journal of Allied Health Sciences, 2021)
Common consensus dictates that the best femoral head that a young patient can have been their own, native femoral head. Physiologic “age” is a somewhat a vague term that takes into account the general health and functional status of the patient. New data have shown that approximately 80% of young patients with displaced femoral neck fractures treated with ORIF are able to preserve their own femoral head for a decade after the original insult. Variables under the surgeon’s control include timing of fixation, quality of reduction, accurate implant placement and implant choice, and capsulotomy. Mrs R, a fifty-five-year-old lady presented with a history of fall at home. She complained of left hip pain and inability to weight bear. Clinically, there was pain overlying the anterior aspect of proximal thigh with limited range of motion of the left hip. Plain radiographs illustrated a left neck of femur fracture. The patient was subsequently treated operatively with a dynamic hip screw of the left hip augmented with a Pauwel screw into the postero-inferior aspect of the head. Posterior inferior comminution significantly affects torque to failure in vertically oriented femoral neck fracture. Post operatively, patient was able to partially weight bear with walking frame. Patient subsequently was walking without aid at 6 weeks and with no evidence of avascular aecrosis on plain radiographs. The author prefers anatomic reduction and subsequent stabilisation with a sliding hip screw and Pauwel screw. Attention to detail is crucial in obtaining anatomic reduction, which is the single, most important variable determining the outcome of these challenging injuries.